1994
DOI: 10.1093/oxfordjournals.humrep.a138783
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and early embryology: Sexual differentiation and preimplantation cell growth

Abstract: Growth rates of human preimplantation embryos fertilized in vitro were assessed and compared to the sex of the pregnancy outcome. The likelihood of a liveborn male was significantly greater than that of a female if the mean number of cells/embryo was four or greater at the scheduled time of transfer (odds ratio of 6:1). This finding suggested that the Y chromosome expresses factors which influence embryonic growth rates immediately after fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 0 publications
5
78
0
1
Order By: Relevance
“…Embryos produced in vitro in a number of species fall into fast-cleaving and slow-cleaving groups, which are predominantly male and female, respectively. This phenomenon has been observed for bovine (1)(2)(3)(4)(5),** mouse (6,7), sheep (8,9), and human embryos (10). In vivo-produced male pig embryos, both before and subsequent to hatching from the zona pellucida, have also been reported to be larger and to have more cells than female embryos (11,12).…”
mentioning
confidence: 68%
“…Embryos produced in vitro in a number of species fall into fast-cleaving and slow-cleaving groups, which are predominantly male and female, respectively. This phenomenon has been observed for bovine (1)(2)(3)(4)(5),** mouse (6,7), sheep (8,9), and human embryos (10). In vivo-produced male pig embryos, both before and subsequent to hatching from the zona pellucida, have also been reported to be larger and to have more cells than female embryos (11,12).…”
mentioning
confidence: 68%
“…Furthermore, it has been postulated that the difference in foal gender is due to different endocrine functions of the fetus, interacting differently with the control of parturition (Jainudeen and Hafez 2000). In human pregnancies, this fact has been associated with differences in androgen action (de Zegher et al 1999) and to sex-chromosome-linked effects (Pergament et al 1994, Monteiro et al 1998). However, there are two older reports which failed to document a significant association between foal gender and GL in horses (Arora et al 1983, El-Wishi et al 1990).…”
Section: Sex Of Foalmentioning
confidence: 99%
“…It is agreed that the male body development is greater than the female's and, therefore, as birth only occurs when the foetal development is complete, the colts' gestation period would be longer, even though Wilsher and Allen (2002) have shown that colts have a better developed placenta, and might, therefore, be expected to develop more quickly. The longer gestation period of colts has been justified as being due to androgen action (Zegher et al, 1999), to different endocrine functions of male and female foetuses interacting differently with the endocrine control of parturition (Jainudeen and Hafez, 2000) and to sex chromosome-linked effects (Pergament et al, 1994).…”
Section: Sex Of the Foalmentioning
confidence: 99%